2007
DOI: 10.1016/j.schres.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lamotrigine augmentation of clozapine in a sample of treatment-resistant schizophrenic patients: A double-blind, placebo-controlled study

Abstract: Based on the evidence that lamotrigine added to clozapine in refractory schizophrenic patients has reported promising results, the present 24-week double-blind, randomized, placebo-controlled trial had the aim to explore the efficacy of lamotrigine add-on pharmacotherapy on clinical symptomatology and cognitive functioning in a sample of treatment-resistant schizophrenic patients receiving clozapine. After clinical and neurocognitive assessments patients were randomly allocated to receive, in a double-blind de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 34 publications
2
45
0
4
Order By: Relevance
“…Tiihonen 79 quantitatively summarized the effect of lamotrigine addition, including the same studies as in this review. As they did not identify Zoccali et al 56 as an outlier, they arrived to a slightly more positive conclusion.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Tiihonen 79 quantitatively summarized the effect of lamotrigine addition, including the same studies as in this review. As they did not identify Zoccali et al 56 as an outlier, they arrived to a slightly more positive conclusion.…”
Section: Discussionmentioning
confidence: 91%
“…Again, Zoccali et al 56 was an outlier. After exclusion, Hedges's g decreased and heterogeneity disappeared.…”
Section: Antiepileptic Medicationmentioning
confidence: 94%
See 1 more Smart Citation
“…An initial study with lamotrigine demonstrated positive effects on cognition (Zoccali et al 2007), but these findings were not replicated in a larger study (Goff et al 2007). Selective phosphodiesterase inhibitors may possibly have beneficial effects on symptoms and on cognition in schizophrenia (Menniti et al 2007).…”
Section: Other Possible Cognitive Enhancersmentioning
confidence: 98%
“…Pharmacotherapies adjunctive to antipsychotic treatment may be useful strategies to control negative symptoms. These include anticonvulsants such as lamotrigine (Zoccali et al, 2007), antioxidants such as N-acetyl cysteine (Berk et al, 2008) and antidepressants. Several studies have reported improvement in negative symptoms when antidepressants are administered as an adjunct to antipsychotics.…”
Section: Introductionmentioning
confidence: 99%